Lentinan-functionalized PBAE-G-nanodiamonds as an adjuvant to induce cGAS-STING pathway-mediated macrophage activation and immune enhancement - Zhiqiang Zhang; Li Wang; Xia Ma; Hui Wang (Journal of Pharmaceutical Analysis)
A series of biodegradable nanoparticle-based drug delivery systems have been designed utilizing poly(β-amino ester)-guanidine-phenylboronic acid (PBAE-G) polymers. In this study, a novel Lentinan-Functionalized PBAE-G-nanodiamond system was developed to carry ovalbumin (LNT-PBAE-G-ND@OVA). The impact of this drug delivery system on the activation and maturation of macrophages was then assessed. Furthermore, LNT-PBAE-G-ND@OVA induced potent antibody response and showed no obvious toxicity in vitro and in vivo. Moreover, treatment with LNT-PBAE-G-ND@OVA was sufficient to alter the expression of genes associated with the cGAS-STING pathway, and the LNT-PBAE-G-ND@OVA induced upregulation of costimulatory molecules. LNT-PBAE-G-ND@OVA treatment was sufficient to induce macrophage activation through a complex mechanism in which cyclic guanosine monophosphate-adenosine monophosphate (cGAMP) synthase (cGAS)-stimulator of interferon genes (STING) signaling plays an integral role.